Serum C-Reactive Protein as a Potential Indicator for Screening Fecal Calprotectin in Patients With Moderate-to-Severe Hidradenitis Suppurativa: A Cross-Sectional Cohort Study - Ogut, Neslihan Demirel; Sagkan, Rahsan Ilikci; Arici, Rabia; Gokyayla, Ece; Unal, Simge; Yildirim, Sema Koc; Ozturk, Ayris (Wiley, 2025)
BackgroundHidradenitis suppurativa (HS) is a chronic inflammatory skin disorder frequently associated with immune-mediated comorbidities, including inflammatory bowel disease (IBD). Given the potential risk of IBD, particularly before initiating therapies such as interleukin (IL)-17 inhibitors, screening through a fecal calprotectin (FC) test may be warranted. While FC is a reliable, non-invasive biomarker for ruling out IBD, its cost and limited availability in dermatology settings present challenges. Therefore, this study aims to investigate the potential association between FC and serum C-reactive protein (CRP) levels in patients with moderate-to-severe HS, which may provide a more accessible screening approach.MethodThis cross-sectional cohort study was conducted at the Department of Dermatology and Venereology of U & scedil;ak University between April 2, 2024, and December 31, 2024, including 18-65-year-old patients with moderate-to-severe HS. Serum CRP and FC levels were analyzed using an enzyme-linked immunosorbent assay (ELISA).ResultsStool samples from 61 patients with moderate-to-severe HS were included. The median FC and serum CRP levels were 28.2 mu g/g and 5.3 mg/L, respectively, with a significant correlation between them (rho = 0.289, p = 0.026). While FC levels did not significantly differ between moderate and severe HS, CRP levels were significantly higher in patients with severe disease (p = 0.009). Receiver operating characteristic (ROC) analysis identified a CRP cut-off of 5.35 mg/L for predicting FC >= 50 mu g/g (AUC = 0.660, p = 0.045), with 70% sensitivity and 61.5% specificity.ConclusionPatients with moderate-to-severe HS and serum CRP levels above 5.35 mg/L may benefit from FC screening, and those with FC levels exceeding 50 mu g/g may be considered for further endoscopic evaluation to assess IBD.
Keywords: C-reactive protein; fecal calprotectin; hidradenitis suppurativa; inflammatory bowel disease